Essential qualities for dental practice: dental students' perspectives in Hong Kong - Jasmine Cheuk Ying Ho; Hollis Haotian Chai; Ivy Guofang Sun; Michelle Zeping Huang; Michelle Zeping Huang; Edward Chin Man Lo; Chun Hung Chu (Frontiers in Oral Health)
ObjectiveThe objective of this quantitative study is to explore the perspectives of dental students in Hong Kong regarding the key qualities that define a good dentist and a successful dentist.MethodsA cross-sectional survey was conducted to Hong Kong dental students in 2024 using an anonymous questionnaire. The questionnaire basically consisted of four self-administered questions. The first two questions examined the qualities that dental students associate with “a successful dentist” and “a good dentist,” respectively. The third question focused on the qualities expected of their dentist, and the fourth question investigated the qualities that dental school training should emphasize. For each question, respondents were requested indicate three key or most essential qualities. They could write down or choose the qualities provided in the list with 24 qualities.ResultsAll 452 students in the dental school were invited and 399 students (88%) completed the survey. “Clinically competent” and “Good communication skills” and “Responsible/accountable” emerged as the top three qualities across the first three questions. They identified “Clinically competent”, “Good communication skills” and “knowledgeable” are three key qualities to be cultivated during training in dental school.ConclusionsHong Kong dental students consider clinically competent, good communication skills, and being responsible/accountable are the key qualities for both good and successful dentists. These are also the key qualities they expected from their own dentist. Additionally, they emphasize the importance for dental schools to provide training that fosters clinical expertise, communication proficiency, and comprehensive knowledge to ensure graduates can deliver high-quality patient care.SignificanceThis survey offers important insights into the key qualities that dental students in Hong Kong believe are important for being a good and successful dentist. These findings can guide dental education to better prepare future professionals. Understanding these perspectives can help align educational goals with professional expectations, improving patient care and job satisfaction.